Bacterial membrane binding and pore formation abilities of carbohydrate recognition domain of fish lectin. (February 2017) - Arasu, Abirami; Kumaresan, Venkatesh; Palanisamy, Rajesh; Arasu, Mariadhas Valan; Al-Dhabi, Naif Abdullah; Ganesh, Munuswamy-Ramanujam; Arockiaraj, Jesu
Abstract: Antimicrobial peptides (AMPs) are innate molecules that are found in a wide variety of species ranging from bacteria to humans. In recent years, excessive usage of antibiotics resulted in development of multi-drug resistant pathogens which made researchers to focus on AMPs as potential substitute for antibiotics. Lily type mannose-binding lectin is an extended super-family of structurally and evolutionarily related sugar binding proteins. These lectins are well-known AMPs which play important roles in fish defense mechanism. Here, we report a full-length lily type lectin-2 (LTL-2) identified from the cDNA library of striped murrel, Channa striatus ( Cs ). Cs LTL-2 protein contained B-lectin domain along with three carbohydrate binding sites which is a prominent characteristic functional feature of LTL. The mRNA transcripts of Cs LTL-2 were predominantly expressed in gills and considerably up-regulated upon infection with fungus ( Aphanomyces invadans ) and bacteria ( Aeromonas hydrophila ). To evaluate the antimicrobial activity of the carbohydrate binding region of Cs LTL-2, the region was synthesized (QP13) and its bactericidal activity was analyzed. In addition, QP13 was labeled with fluorescein isothiocyanate (FITC) and its binding affinity with the bacterial cell membranes was analyzed. Minimum inhibitory concentration assay revealed that QP13 inhibited the growth of Escherichia coli at a concentration of 80 μM/ml. Confocal microscopic observation showed that FITC tagged QP13 specifically bound to the bacterial membrane. Fluorescence assisted cell sorter (FACS) assay showed that QP13 reduced the bacterial cell count drastically. Therefore, the mechanism of action of QP13 on E. coli cells was determined by propidium iodide internalization assay which confirmed that QP13 induced bacterial membrane disruption. Moreover, the peptide did not show any cytotoxicity towards fish peripheral blood leucocytes. Taken together, these results support the potentiality of QP13 that can be used as an antimicrobial agent against the tested pathogens. Highlights: An AMP QP13 was synthesized from lily type lectin 2 of murrel. Binding affinity of QP13 labeled with FITC was analyzed. Confocal observation showed FITC tagged QP13 bound to bacterial membrane. FACS showed QP13 reduced the bacterial cell count drastically. PI internalization confirmed QP13 induced membrane disruption.